Role of PTPN22 and CSK gene polymorphisms as predictors of susceptibility and clinical heterogeneity in patients with Henoch-Schönlein purpura (IgA vasculitis). Issue 1 (December 2015) - López-Mejías, Raquel; Genre, Fernanda; Remuzgo-Martínez, Sara; Pérez, Belén; Castañeda, Santos; Llorca, Javier; Ortego-Centeno, Norberto; Ubilla, Begoña; Mijares, Verónica; Pina, Trinitario; Calvo-Río, Vanesa; Palmou, Natalia; et al.
Abstract Introduction To determine whether the PTPN22 (protein tyrosine phosphatase nonreceptor 22)/CSK (c-src tyrosine kinase) pathway is implicated in the susceptibility and clinical heterogeneity of Henoch-Schönlein purpura (HSP) in the largest series of Caucasian HSP patients ever assessed for genetic studies. Methods A set of 329 Spanish patients diagnosed with HSP fulfilling the American College of Rheumatology and the Michel et al. classification criteria and 515 sex and ethnically matched controls were recruited in this study. Two well-knownCSK (CSK rs34933034 andCSK rs1378942) and two functionalPTPN22 (PTPN22 rs2476601 (R620W) andPTPN22 rs33996649 (R263Q)) polymorphisms, previously associated with autoimmunity, were genotyped with TaqMan single nucleotide polymorphism (SNP) genotyping assays. Results No significant differences in the genotype and allele frequencies between HSP patients and controls were observed when theCSK rs34933034, CSK rs1378942, PTPN22 rs2476601 (R620W) andPTPN22 rs33996649 (R263Q) polymorphisms were analyzed independently. In keeping with this observation, no significant differences were found when we assessed these polymorphisms combined conforming haplotypes. In addition, there were no differences in the allele or genotype frequencies when HSP patients were stratified according the age at disease onset, sex, presence of arthralgia/arthritis, nephritis or gastrointestinal manifestations. Conclusions Our results do not support association betweenPTPN22/CSK and HSP.